2008
DOI: 10.1007/s10482-008-9243-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and functional properties of a novel lipomannan variant isolated from a Corynebacterium glutamicum pimB′ mutant

Abstract: The genus Corynebacterium is part of the phylogenetic group nocardioform actinomycetes, which also includes the genus Mycobacterium. Members of this phylogenetic group have a characteristic cell envelope structure, which is dominated by complex lipids and amongst these, lipoglycans are of particular interest. The disruption of NCgl2106 in C. glutamicum resulted in a mutant devoid of monoacylated phosphatidyl-myo-inositol dimannoside (Ac 1 PIM 2 ) resulting in the accumulation of Ac 1 PIM 1 and cessation of pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
44
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 43 publications
2
44
0
Order By: Relevance
“…4) using a Pro-Q emerald glycoprotein stain according to an established protocol (15,25). Extracts from C. glutamicum showed the presence of LAM Cg as well as LM-A Cg and LM-B Cg (which comigrates with LM-A Cg ), as shown previously (16,25). The lipoglycan extract from C. glutamicum ⌬pimBЈ showed the absence of LAM Cg and LM-A Cg and the presence of Man GlcAGroAc 2 -based LM-B Cg (16), while C. glutamicum ⌬mgtA showed the presence of the PI-based lipoglycans LAM Cg and LM-A Cg and the absence of LM-B Cg (25).…”
supporting
confidence: 72%
See 2 more Smart Citations
“…4) using a Pro-Q emerald glycoprotein stain according to an established protocol (15,25). Extracts from C. glutamicum showed the presence of LAM Cg as well as LM-A Cg and LM-B Cg (which comigrates with LM-A Cg ), as shown previously (16,25). The lipoglycan extract from C. glutamicum ⌬pimBЈ showed the absence of LAM Cg and LM-A Cg and the presence of Man GlcAGroAc 2 -based LM-B Cg (16), while C. glutamicum ⌬mgtA showed the presence of the PI-based lipoglycans LAM Cg and LM-A Cg and the absence of LM-B Cg (25).…”
supporting
confidence: 72%
“…Using Rv0557 as a query sequence in a BLAST comparison, the next paralog among the six members of M. tuberculosis within the GT4 family was Rv2188c (identity score, 35%), revealing a structural similarity between the two proteins. Both proteins possess orthologs in C. glutamicum, and previous genetic and biochemical studies confirmed that the orthologous proteins have identical functions (13,16,25). When either pimBЈ Cg or mgtA Cg was deleted, no reliable growth defect was observed (data not shown).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…1B). Although both pathways share many common enzymes, LM-A species are based on a glucopyranosyluronic acid diacylglycerol (Gl-A) anchor rather than PI (16,18). On the cytoplasmic side, Gl-A is mannosylated by MgtA (previously named PimB), producing mannosyl-glucuronic acid diacylglycerol (Gl-X), which is extended by MptB (17,29) and other enzymes common to both pathways to produce LM-B, the major LM pool of C. glutamicum (37,38).…”
mentioning
confidence: 99%
“…This pathway shares some PPM-dependent enzymes with the PI-based LM pathway including MptB, since an mptB (NCgl1505) mutant of C. glutamicum fails to produce intermediates beyond Gl-X or AcPIM2 [133]. For clarity, the PI-based LM pool has been designated LM-A while this second pathway produces LM-B [121,146], the major LM pool in C. glutamicum [118]. While C. glutamicum produces LAMs via LM-A using a similar pathway to mycobacteria, its LAMs are smaller and structurally distinct, with more extensive mannosylation and singular Araf capping [147].…”
Section: Lm/lammentioning
confidence: 99%